2019
DOI: 10.1177/0361198119842110
|View full text |Cite
|
Sign up to set email alerts
|

YouTube as a Source of Information in Understanding Autonomous Vehicle Consumers: Natural Language Processing Study

Abstract: The automotive industry is currently experiencing a revolution with the advent and deployment of autonomous vehicles. Several countries are conducting large-scale testing of autonomous vehicles on private and even public roads. It is important to examine the attitudes and potential concerns of end users towards autonomous cars before mass deployment. To facilitate the transition to autonomous vehicles, the automotive industry produces many videos on its products and technologies. The largest video sharing webs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Results showed that there is no consensus among the public on trust in AVs (Salonen & Haavisto, 2019), with more studies highlighting a lack of trust in AVs than a high level of trust in them. For studies that undertook qualitative analysis, the word trust was one of the words with the highest frequencies, which implies a lack of trust in AVs, especially for frequent drivers (Cho & Jung, 2018;Das et al, 2019). The results also showed that trust may vary depending on the reliability.…”
Section: Iii34 Perceptionsmentioning
confidence: 95%
See 2 more Smart Citations
“…Results showed that there is no consensus among the public on trust in AVs (Salonen & Haavisto, 2019), with more studies highlighting a lack of trust in AVs than a high level of trust in them. For studies that undertook qualitative analysis, the word trust was one of the words with the highest frequencies, which implies a lack of trust in AVs, especially for frequent drivers (Cho & Jung, 2018;Das et al, 2019). The results also showed that trust may vary depending on the reliability.…”
Section: Iii34 Perceptionsmentioning
confidence: 95%
“…The perceived safety varied according to the level of automation, but the meaning of this effect was interpreted differently. Some researchers showed that perceived safety decreased significantly with an increase in automation level (Das et al, 2019;Brell et al, 2019b;Nees, 2019) whereas other researchers found that perceived safety was higher for highly or fully AVs (Lee & Kolodge, 2019;Pettigrew et al, 2019). These results were corroborated by showing that AV technology was positively evaluated, created a perceived safety improvement and allowed drivers to be more relaxed (Lu et al, 2017;Kauer et al, 2015;Nishihori et al, 2017).…”
Section: Iii34 Perceptionsmentioning
confidence: 97%
See 1 more Smart Citation
“…Another worthwhile study of topic modeling in the transportation field was conducted by Das et al (25) in which they studied topic changes of abstracts from papers presented at the TRB Annual Meeting from 2008 to 2014. Das et al used text mining and topic modeling in several other transportation studies (26)(27)(28)(29). Two recent studies used text mining and topic modeling TRB compendium papers and TRR papers (30,31).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, several studies have incorporated text mining in transportation engineering research: consumer complaint analysis ( 24 , 25 ), understanding public sentiments on safety enhancement and bike sharing ( 26 , 27 ), identifying research trends from transportation engineering conference papers and journals ( 28 – 32 ), crash narrative investigation ( 33 – 38 ), text analytics using social media mining ( 25 , 33 , 3941 ), and transportation-related surveys ( 42 , 43 ). Ghazizadeh et al used text mining and latent Dirichlet analysis (LDA) to identify key patterns and non-trivial knowledge from the NHTSA complaint database.…”
Section: Earlier Work and Research Contextmentioning
confidence: 99%